The Prognostic Value of Body Fat Components in Metastasis Renal Cell Carcinoma Patients Treated with TKIs - Dai, Jindong (Cancer Manag Res, 2020)
PURPOSE: To assess the association between body fat components and survival status and tumor response for metastatic renal cell carcinoma (mRCC) patients treated with tyrosine kinase inhibitors (TKIs). PATIENTS AND METHODS: Patients with pathologically diagnosed and radiologically indicated mRCC were enrolled into the retrospective study. Three body fat components: total fat accumulation (TFA), visceral fat accumulation (VFA) and subcutaneous fat accumulation (SFA) were measured using standard CT scans. The clinical outcomes included progression-free survival (PFS), overall survival (OS), and tumor response rates. Univariate analysis and multivariate Cox proportion hazard regression models were used to find associated parameters and to calculate the adjusted hazard ratio (HR). RESULTS: A total of 146 patients were enrolled and the average age of patients was 56.5 years old. According to the univariate analysis, patients with an increased SFA and TFA had a longer PFS and OS. A similar phenomenon was observed among patients with ≥2 increasing body fat components about PFS and OS. As for multivariate analysis, SFA change (p=0.014) or the number of increasing body fat components (p=0.040) were independent indicators to predict PFS. In addition, SFA change (p=0.022) or the number of increasing body fat components (p=0.008) could independently predict OS. Moreover, a better disease control rate (p=0.028) was founded in patients with ≥2 increasing components. In the subgroup of patients with ≥2 metastasis sites, improved OS (p=0.017) and PFS (p=0.027) were found compared to those with <2 increasing components. Further multivariate analysis identified the number of increasing body fat components was an independent factor in predicting PFS (p=0.018) and OS (p=0.029). CONCLUSION: Body fat accumulation, such as high SFA or TFA at progression, could improve the survival of patients with mRCC treated with TKIs, especially patients with higher tumor burden. It should be considered as an important parameter to predict the survival status of patients with mRCC.